Infrastructure and reproduction approach to research intellectual infrastructure of technological development - E. V. Yakovleva (Омский научный вестник: Серия "Общество. История. Современность")
The infrastructure and reproduction methodological approach is presented as a tool of research of intellectual infrastructure of technical and technological development of industrial enterprises in conditions of globalization of economy digitisation. The relevance of the results of the study consists in the possibility of implementing, on the basis of the proposed approach, many tasks of scientific and practical importance, which allow to develop methods, systems, algorithms, mechanisms of intra-firm formation and development of the intercompany infrastructure of technologization. The essence of the approach is to ensure system organization of personnel management of industrial enterprises to the level of management of personnel reproduction cycles, which are infrastructure-relevant for technological development of enterprises